Innovation patterns under the magnifying glass: Firm-level latent class analysis of innovation activities in services - Alexandre Trigo (The University of Manchester, Manchester Business School, 2009)
Innovation is still an obscure concept although many efforts have been made to improve the understanding and measurement of it. The growth of service activities throughout the economy has encouraged scholars, policy makers and executives to explore the determinants and features of the innovation developed by service enterprises. Many empirical studies that form the basis of recent literature on innovation in services have proved the existence of a wide range of innovation patterns, confuting the initial assumption that all services are supplier-dominated. In this sense, innovation in services cannot be analysed using a one-size-fits-all concept and that these activities have different innovative trajectories. This paper aims to analyse the real scope of diversity in innovation patterns in services regarding innovation activities and outputs. The empirical analysis is based on the Fourth Community Innovation Survey for Spain. In order to identify clusters with similar behaviour patterns as far as innovation activities and outputs are concerned, we will use the latent class analysis as alternative method of clustering. Firm-level analyses have permitted the in-dept scrutinisation of innovation patterns, beyond the boundary of the traditional standard industrial classification largely applied so far. The empirical results led to create an innovation typology for services, derived from innovation activities and the types of innovation developed, what is composed of four profiles: Knowledge Creator, Knowledge Adopter, Knowledge Creator and Adopter and Neither Creator nor Adopter of Knowledge. From the viewpoint of public innovation policies, the diversity of innovation patterns found encourages the development of tools based on sectoral differences in terms of the nature of the innovation process and the technological opportunities and products.
Keywords: 330; innovation patterns; latent class analysis; service sector; R&D; training activities